Revision of N(2)O-Producing Pathways in the Ammonia-Oxidizing Bacterium Nitrosomonas europaea ATCC 19718 - Kozlowski, Jessica A. (American Society for Microbiology, 2014)
Nitrite reductase (NirK) and nitric oxide reductase (NorB) have long been thought to play an essential role in nitrous oxide (N(2)O) production by ammonia-oxidizing bacteria. However, essential gaps remain in our understanding of how and when NirK and NorB are active and functional, putting into question their precise roles in N(2)O production by ammonia oxidizers. The growth phenotypes of the Nitrosomonas europaea ATCC 19718 wild-type and mutant strains deficient in expression of NirK, NorB, and both gene products were compared under atmospheric and reduced O(2) tensions. Anoxic resting-cell assays and instantaneous nitrite (NO(2)(−)) reduction experiments were done to assess the ability of the wild-type and mutant N. europaea strains to produce N(2)O through the nitrifier denitrification pathway. Results confirmed the role of NirK for efficient substrate oxidation of N. europaea and showed that NorB is involved in N(2)O production during growth at both atmospheric and reduced O(2) tensions. Anoxic resting-cell assays and measurements of instantaneous NO(2)(−) reduction using hydrazine as an electron donor revealed that an alternate nitrite reductase to NirK is present and active. These experiments also clearly demonstrated that NorB was the sole nitric oxide reductase for nitrifier denitrification. The results of this study expand the enzymology for nitrogen metabolism and N(2)O production by N. europaea and will be useful to interpret pathways in other ammonia oxidizers that lack NirK and/or NorB genes.